A Review of Current Concepts In Cancer Chemotherapy - Smaldone, Laurie F.; Carter, Stehen K. (Revista Brasileira de Cancerologia, 2023)
Chemotherapy today is a modality predominantly used to treat metastatic or disseminated malignant neoplastic disease. Depending upon the primary site and stage (extent) of disease, chemotherapy can be geared to be curative or palliative in its intent. Chemotherapy can lead to prolonged disease-free survival in a percentage of patients with certain stages of eieven different malignancies (Table 1). For some of these, chemotherapy can eradicate all malignancy by itself in advanced stages when macroscopic metastatic disease is present. For the three pediatric solid tumors on the list, chemotherapy is used as an adjuvant to surgery and/or irradiation to eradicate microscopic metastatic disease after the local modalities have removed or abiated the primary local and residual disease.